Provision and assessment properties of nanoliposomes containing macroalgae extracts of Sargassum boveanume and Padina pavonica. (1st February 2023) - Feng, Yan; Zarei, Vahid; Mousavipour, Nesa
Abstract: Seaweeds have a high potential to use in various industries such as pharmaceuticals and foods due to having unique bioactive properties. Bioactive compounds are easily decomposed in contact with heat and light. Therefore, encapsulation can be an effective method to preserve the stability of the antioxidant properties of bioactive compounds. This study was conducted to fabricate and evaluate the properties of nanoliposomes containing algae extracts Sargassum boveanum (LS) and Padina pavonica (LP) by the thin layer dehydration method. Afterward, four formulations with different soybean lecithin and cholesterol ratios were fabricated to determine the optimal formulation for encapsulating algae extracts. The image of FESEM shows that the aqueous extracts of algae were successfully encapsulated in nanoliposomes, and spherical vesicles were without fracture. The DLS data on optimal formulations showed particle size in nanoliposomes containing extracts of LP and LS according to D (90) are 180 nm and 242 nm, respectively. The results for the loading efficiency indicated that formulations F1 for Sargassum extract and F4 for Padina extract with loads of 83.9% had an optimal performance. Furthermore, algae extract release test results in 72 h showed that the extracts encapsulated with nanoliposomes performed much lower and slower releasing than the free extract. Highlights: Encapsulating algae extracts could prevent phenolic components from oxidizing. The encapsulation efficiency of Sargassum and Padina extracts using Nanoliposomes was 83.9%. The release rate of phenolic extracts was controlled by nanoliposomes in 72 h.